One-year efficacy and safety of the Trufill DCS Orbit and Orbit Galaxy detachable coils in the endovascular treatment of intracranial aneurysms: Results from the TRULINE study. Issue 5 (October 2017) - Gory, Benjamin; Huot, Laure; Riva, Roberto; Labeyrie, Paul E; Levrier, Olivier; Lebedinsky, Ariel; Brunel, Hervé; Gauvrit, Jean-Yves; Blanc, Raphael; Chabert, Emmanuel; Derex, Laurent; Emery, Evelyne; et al.
Background and purpose: No series reported the mid-term results of Trufill DCS Orbit and Orbit Galaxy detachable coils with independent evaluation. We present the one-year safety and efficacy of these coils in real-life routine clinical practice. Methods: A total of 167 patients with 167 aneurysms (39.1% ruptured) were enrolled in the prospective TRULINE study. The primary endpoint was the safety, assessed by the combined morbidity-mortality rate observed since the time of the procedure and up to one-year follow-up. For safety, primary analyses were performed on intent-to-treat population (attempted coils procedure) and all adverse events have been reviewed by an independent Data Safety Monitoring Board. For efficacy, primary analyses were performed on the per-protocol population (patients treated with more than 70% of Trufill coils and not retreated during the follow-up period) and an independent core laboratory evaluated angiographic results. Results: At one-year post-procedure, neurologic impairment was observed in 6.5% (95% confidence interval: 3.5–11.8) of the patients, and 2.6% (95% confidence interval: 1.0–6.8) had a permanent neurological deterioration. Three deaths were observed, unrelated to the procedure or coils. At one year, complete occlusion was seen in 52 aneurysms (54.2%), neck remnant in 28 aneurysms (29.2%), and aneurysm remnant in 16 aneurysms (16.7%). During the one-year follow-up, the overall incidence of recurrence was 30.2% with a mean interval of 13.8 ± 4.5 months and the retreatment for major recanalization was needed in nine patients (6.3%). Conclusions: The TRULINE study confirms that endovascular coiling with Trufill DCS Orbit and Orbit Galaxy detachable coils is safe and effective.